Kompetent für das Studium!? Eignung und Gesundheit im Studium der Lernbehindertenpädagogik - Dr. Schmid, Andrea Christine (Verlag Julius Klinkhardt, 2015)
The research project ""Aptitude and Health in the Study of Education for Learning Disabilities"" (EGIS-L) investigates the question of what aptitude students have for the chosen study programme and how they perceive and cope with the challenges and stresses involved. The research focus is on the areas of personal competence development and self-regulation, as well as health promotion and spirituality. The long-term study will also investigate the extent to which the findings have changed and developed from the beginning of the study programme after the intensive internship year to the end of the study programme. The research results, which were collected and interpreted methodologically in standardised written surveys and qualitative interviews, can provide important information for professionalisation research in the area of the first phase of special needs teacher education. Thus, an innovative contribution is to be made for the development and updating of special needs education study programmes.